2014
DOI: 10.1007/s10152-014-0404-5
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and biological features of the common pandora, Pagellus erythrinus (Linnaeus, 1758), in the southern Tyrrhenian Sea (Central Mediterranean)

Abstract: A synthetic analysis of the distribution, abundance and some biological traits of the common pandora (Pagellus erythrinus) was performed. Data were gathered in 15 experimental bottom trawl surveys carried out off the southern Tyrrhenian Sea from 1994 to 2008. A total of 2,166 P. erythrinus were found in the investigated area, with a preference for the upper continental shelf (10-100 m). The highest persistence was recorded in the trawl-banned areas. The sex ratio Sr = F/(F ? M) ranged between 0.60 and 0.96 (ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Length at first maturity (L 50 ) estimated in western Algerian coast for Pagellus erythrinus is lowest than those observed in Tunisia 15.32cm (Ben smida & Hadhri., 2014); Tyrrhénian sea 15.7cm (Busalacchi et al, 2014); Portugal 17.29cm (Coelho et al, 2010); and higher than those found by (Metin et al, 2011) in the central Aegean Sea 11.30cm.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Length at first maturity (L 50 ) estimated in western Algerian coast for Pagellus erythrinus is lowest than those observed in Tunisia 15.32cm (Ben smida & Hadhri., 2014); Tyrrhénian sea 15.7cm (Busalacchi et al, 2014); Portugal 17.29cm (Coelho et al, 2010); and higher than those found by (Metin et al, 2011) in the central Aegean Sea 11.30cm.…”
Section: Discussionmentioning
confidence: 57%
“…The predominance of females can be explained by protogynous hermaphroditism and an abundance of young individuals among the stock (Metin., 2011). The presence of small sized males (primary males) and large females in our samples suggests that sex change does not occur in each individual (Busalacchi et al, 2014).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Pagellus erythrinus (Linnaeus, 1758) is a common fish species with a wide distribution in the Mediterranean, Black Sea, and the eastern Atlantic Ocean, from Scandinavia to Cape Verde (Fischer et al 1987). It is found in depths up to 320 m, while most commonly it occupies the depth range between 10 m and 100 m (Somarakis & Machias 2002;Spedicato et al 2002;Busalacchi et al 2014). Pagellus erythrinus is mainly a protogynous hermaphroditic fish (Buxton & Garratt 1990).…”
Section: Introductionmentioning
confidence: 99%